A Novel Follicular Unit Excision Device for All-Purpose Hair Graft Harvesting - Umar S; Lohlun B; Ogozuglu T; Carter MJ (Dove Medical Press, 2021)
Sanusi Umar,1– 3 Boudine Lohlun,4 Tayfun Ogozuglu,5 Marissa J Carter6 1Department of Medicine, Dermatology Division, University of California, Los Angeles, CA, USA; 2Division of Dermatology, Harbor-UCLA Medical Center, Torrance, CA, USA; 3Dr. U Hair and Skin Clinic, Manhattan Beach, CA, USA; 4HairFront Clinic, Cape Town, South Africa; 5Dr. T Hair Transplant, Istanbul, Turkey; 6Strategic Solutions, Inc., Bozeman, MT, USACorrespondence: Sanusi UmarDr. U Hair and Skin Clinic, 2121 N. Sepulveda Boulevard, Suite 200, Manhattan Beach, CA, 90266, USATel +1-310-318-1500Fax +1-310-318-1590Email drumar@dru.comPurpose: A challenge in follicular unit excision (FUE) is the lack of a single device that can adequately meet the requirements of a range of patient donor variables, such as hair curliness, race, body and head hair locations, and non-shaven short- and long-hair FUE. This study aimed to describe a novel FUE device developed based on skin responsiveness to serve as a single all-purpose FUE donor harvester.Patients and Methods: We describe an all-purpose FUE device that consists of an all-purpose punch and a functionally complementing punch driver. The mechanism of action and method of use are reported. Several patients with a diversity of FUE challenges for three experienced FUE practitioners using the novel device are presented using photos and videos. The practitioners also reported their comparative experiences with using prior FUE systems in similar situations.Results: The novel device demonstrated success in a variety of FUE scenarios without requiring specialized provider skills. The device responds to changing skin firmness and thickness, which are the primary causes of inconsistent performance in FUE devices between patients and within patients from one body/head area to another. It also minimized challenges of unpredictable hair curliness and angles by its innate ability to self-navigate the subsurface course of hair follicles, to which the FUE practitioner is typically blinded.Conclusion: We describe a novel FUE device that overcomes the challenges of previous FUE technologies and has potential applicability to a diverse range of FUE scenarios. Our experience suggests that further validation is warranted.Keywords: follicular unit extraction, hair transplant, African American, long hair, curly hair, body hair, non-shaven